Current Distribution of the Turkestan White Stork (Ciconia ciconia asiatica) in Kazakhstan - Vassiliy Fedorenko; Yuliya Zima (International Journal of Zoology)
Over the last 100 years, the range of the White Stork Ciconia ciconia asiatica (Linnaeus, 1758) in Kazakhstan has greatly diminished; it has entirely disappeared in its former eastern and northern ranges, while the number of nesting sites has decreased in the remaining part of its habitat. The most recent specialized studies on the distribution of the White Stork here were conducted in the 1980s. Subsequently, ornithologists were only aware of isolated nests, and in the last 15 years, up until recently, in Kazakhstan, there was only one known active nest in the Zhambyl region. To clarify the current distribution of the White Stork in Kazakhstan, we conducted field research during the breeding season in places of its former distribution in the Zhambyl and Turkestan Regions. Nest surveys were conducted by visual observations using binoculars and a camera with a telephoto lens. During the expedition, 43 inhabited nests of the White Stork were found; information about another 4 nests was obtained from data survey and social networks. Analysis of satellite images allowed us to identify 12 nests located on power line pylons in the southern regions of the republic, specifically in the Keles, Zhetisay, and Maktaaral districts. In total, 59 White Stork nests were found in Kazakhstan. In addition, satellite images revealed more than 120 power line pylons with White Stork nests in the territory of Uzbekistan in close proximity to the Kazakhstan border. All literary and electronic sources available to the authors have been meticulously reviewed. By synthesizing these data, two maps were created: one delineating all recorded White Stork nesting sites across Kazakhstan and its neighboring territories, and the other illustrating the known contemporary and historical ranges of the White Stork in Kazakhstan. A cadastral survey accompanies new nest discoveries of the White Stork. Based on the newly acquired data, we conclude that the White Stork population in Kazakhstan is currently on the rise.